A highly efficient heat-insulating LOW-E coated glass for buildings
By adopting a multi-layer structure on LOW-E coated glass, including Ag-Cu alloy film layer and other material layers, the problems of insufficient scratch resistance, wear resistance and corrosion resistance in the prior art are solved, and efficient heat insulation and excellent optical properties are achieved, suitable for building and automotive windows.
Patent Information
- Application Number
- CN202411715652.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-01
AI Technical Summary
The existing LOW-E coated glass has shortcomings in its scratch resistance, wear resistance and corrosion resistance, and it is difficult to meet the needs of building energy conservation and environmental adaptability.
The multi-layer structure of Ag-Cu alloy thin film layer, PC/HC/TiO2 composite layer, Ti layer, Ti layer, TiO2 layer, SiO2 layer and HC2 layer is used to deposit these layers through magnetron sputtering and electron beam evaporation technology to improve the optical performance, scratch resistance and wear resistance, as well as corrosion resistance of the glass.
Achieve efficient heat insulation, excellent optical properties, improved scratch and wear resistance, as well as significantly enhanced corrosion and environmental resistance, suitable for low-radiation coatings for building and automotive windows.
Smart Images

Figure HDA0005156826590000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coated glass, and in particular to a high-efficiency heat-insulating LOW-E coated glass for buildings. Background Art
[0002] LOW-E (low-emissivity) coating is an advanced thin film technology applied to glass surfaces to reduce the transfer of heat radiation and improve the energy efficiency of glass. This technology is widely used in building energy conservation, automotive industry, electronic display and other fields. By effectively controlling the transmission of infrared and ultraviolet rays by glass, it makes indoor temperature easier to control, thereby achieving the purpose of energy saving.
[0003] Development of LOW-E coating technology: LOW-E coating technology began in the 1970s. With the increasing demand for energy conservation and environmental protection, the technology has developed rapidly. The initial LOW-E coating technology was based on a single-layer metal oxide film, which was mainly used to reduce infrared radiation outside the visible light range. With the advancement of material science and thin film deposition technology, modern LOW-E coatings usually adopt a multi-layer structure, including silver, zinc oxide, silicon dioxide and other materials, deposited by vacuum sputtering, magnetron sputtering, chemical vapor deposition (CVD) and other processes. Summary of the invention
[0004] In order to overcome the above-mentioned defects of the prior art, the present invention provides a high-efficiency heat-insulating LOW-E coated glass for construction, which can improve optical performance, scratch resistance, wear resistance, and corrosion resistance.
[0005] In order to achieve the above-mentioned purpose of the invention, the present invention provides a high-efficiency heat-insulating LOW-E coated glass for construction, comprising a glass substrate, on which are arranged in sequence an Ag-Cu alloy thin film layer, a PC / HC / TiO2 composite layer, a Ti layer, a TiO2 layer, a SiO2 layer and an HC2 layer, the TiO2 layer, the Ti layer and the SiO2 layer are all deposited by a magnetron sputtering system, the Ag-Cu alloy thin film layer is deposited on the glass substrate by electron beam evaporation technology, the Ag-Cu alloy thin film layer is an Ag70Cu30 alloy thin film, and the thickness of the Ag-Cu alloy thin film layer is 10nm.
[0006] Furthermore, the method for processing the glass substrate includes:
[0007] The glass substrate is placed in an ultrasonic cleaning machine and cleaned for more than 6 minutes using a solution prepared by Deconex and deionized water in a ratio of 3:97 to remove any impurities on the glass substrate;
[0008] After cleaning, the glass substrate is rinsed with deionized water and blown dry with compressed air;
[0009] Then, the glass substrate was placed in a plasma cleaner for plasma cleaning for more than 2 minutes, and then cleaned using an Electronic Diener cleaner.
[0010] Furthermore, the Ag-Cu alloy film deposition method includes:
[0011] Depositing Ag, Cu and Ag-Cu alloy thin films on the glass substrate using electron beam evaporation technology;
[0012] The deposition of Ag and Cu was carried out on a Satis Vacuum model 725 equipment equipped with an ion gun and two electron beams;
[0013] Ag and Cu pellets were placed in two tungsten crucibles, and the substrate was fixed on a rotating bracket 530 mm away from the evaporation source;
[0014] During deposition, the pressure was 9.5×10 -6 mbar. During the evaporation process, an ion gun was used with an Ar flow rate of 13 sccm, and the pressure rose to 1.0×10 -4 mbar;
[0015] The glass substrate is rotated at a speed of 9 rev / min and maintained at a temperature of 100° C.;
[0016] Film thickness was monitored using two independent quartz crystal monitors and later confirmed with a Bruker Dektak XT stylus profilometer;
[0017] The deposition rates of Ag and Cu were controlled by adjusting the deposition rate, and the chemical composition was finally confirmed by X-ray photoelectron spectroscopy.
[0018] Furthermore, when the TiO2 layer is deposited by magnetron sputtering, the deposition parameters are as follows: power 4000 W, Ar flow rate 400 sccm, O2 flow rate 35 sccm, working pressure 5.0×10 -4 mbar, and the thickness is 39.7nm.
[0019] Furthermore, when the Ti layer is deposited by magnetron sputtering, the deposition parameters are as follows: power is 1200 W, Ar flow rate is 400 sccm, and working pressure is 5.0×10 -4 mbar, and the thickness is 6.3nm.
[0020] Furthermore, when the SiO2 layer is deposited by magnetron sputtering, the deposition parameters are as follows: power is 2000 W, Ar flow rate is 230 sccm, O2 flow rate is 45 sccm, working pressure is 3.3×10-3 mbar, and thickness is 10 nm.
[0021] Furthermore, the method for processing the HC2 layer includes:
[0022] The glass substrate provided with the Ag-Cu alloy thin film layer, the PC / HC / TiO2 composite layer, the Ti layer, the TiO2 layer, and the SiO2 layer was dip-coated using a dip coater, and transparent HC2 was coated. The dip-coated sample was vertically dried in a fume hood for 20 minutes and then baked at 130° C. for more than 1 hour to solidify.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Optical performance:
[0025] The 10nm thick Ag-Cu alloy thin film layer has a solar-weighted transmittance of 76% in the visible light range and a solar-weighted light blocking of 39% in the infrared range; it has high transmittance in the visible light region and high reflectivity in the infrared region;
[0026] 2. Anti-scratch and abrasion resistance:
[0027] The alloyed Ag70Cu30 film exhibits higher scratch and wear resistance than pure silver film; in the nano scratch test, the Ag70Cu30 film is superior to the pure silver film in adhesion to TiO2 and hardness;
[0028] 3. Corrosion resistance:
[0029] The Ag70Cu30-based low-emissivity coating showed high corrosion resistance in the salt spray corrosion test, with little change in optical performance after 250 hours (TVIS decreased by 1%, RIR decreased by 11%), and no pitting corrosion. The pure silver-based coating began to corrode after 48 hours, and the optical performance decreased significantly after 250 hours (TVIS decreased by 15%, RIR decreased by 24%).
[0030] 4. Environmental resistance:
[0031] The coated glass exhibits good weather resistance in acid rain and high-salt and high-humidity environments, and is suitable for low-emissivity coatings on the surfaces of automobiles and building windows. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.
[0034] like Figure 1 As shown, a high-efficiency heat-insulating LOW-E coated glass for construction includes a glass substrate 1, on which are sequentially arranged an Ag-Cu alloy thin film layer 2, a PC / HC / TiO2 composite layer 3, a Ti layer 4, a TiO2 layer 5, a SiO2 layer 6 and a HC2 layer 7. The TiO2 layer 5, the Ti layer 4 and the SiO2 layer 6 are all deposited by a magnetron sputtering system. The Ag-Cu alloy thin film layer 2 is deposited on the glass substrate 1 by electron beam evaporation technology. The Ag-Cu alloy thin film layer 2 is Ag70 Cu30 alloy film, the thickness of Ag-Cu alloy film layer 2 is 10nm; the 10nm thick Ag70Cu30 film has a solar weighted transmittance (TVIS) of 76% in the visible light range and a solar weighted blocked light (BLIR) of 39% in the infrared range, has high transmittance in the visible light region and high reflectivity in the infrared region, and the Ag70Cu30-based low-emissivity coating exhibits high corrosion resistance in the salt spray corrosion test, and the alloyed Ag70Cu30 film exhibits higher scratch and wear resistance than pure silver film;
[0035] PC / HC / TiO2 is a composite material consisting of polycarbonate (PC), hard coating (HC) and titanium dioxide (TiO2). This material combines the characteristics of each component to improve the performance of the material;
[0036] Combining these three materials together can produce composite materials with excellent comprehensive properties. For example, PC / HC / TiO2 composite materials may have the following properties:
[0037] High transparency: Maintaining high transparency of polycarbonate, suitable for applications requiring transparent performance;
[0038] High hardness and wear resistance: Hard coating can improve the hardness and wear resistance of the material surface and extend its service life;
[0039] Photocatalytic properties: The photocatalytic properties of titanium dioxide can be used in applications such as air purification and self-cleaning surfaces;
[0040] This composite material may be used in various applications, such as high-performance optical materials, scratch-resistant surface materials, photocatalytic materials, etc.
[0041] Low-E coated glass has a multi-layer film structure, in which the Ag-Cu alloy thin film layer 2 is a key low-emissivity material responsible for reflecting infrared rays and reducing heat transfer, and the metal oxide layer (such as the TiO2 layer 5) is used as an anti-reflection layer to ensure high light transmittance while enhancing the protection of the silver layer. Through the design of the multi-layer film structure, the thickness and material combination of each layer are precisely controlled to achieve a better balance between optical performance and thermal performance;
[0042] Magnetron sputtering is the most widely used process at present. It bombards the target material with high-energy particles, causing the material atoms to detach and deposit to form a uniform coating.
[0043] The multi-layer film structure of LOW-E coated glass makes the coated glass have strong oxidation resistance, corrosion resistance and wear resistance, so as to maintain the same performance under various climatic conditions. To this end, researchers usually add a protective oxide layer on the silver layer or use special packaging technology to enhance the durability of the coating;
[0044] The spectral selectivity of the multi-layer film structure of LOW-E coated glass means that the coating can effectively block infrared and ultraviolet rays while maximally transmitting visible light. This feature requires precise control of the material and thickness of each layer when designing the coating to ensure that the coating has the ability to selectively transmit or reflect light of different wavelengths. Spectral selectivity is the core performance of the multi-layer film structure, which directly affects its energy-saving effect and visual comfort.
[0045] The processing method of the glass substrate 1 includes:
[0046] The glass substrate 1 is placed in an ultrasonic cleaning machine and cleaned for more than 6 minutes using a solution prepared by using Deconex and deionized water in a ratio of 3:97 to remove any impurities on the glass substrate 1;
[0047] After cleaning, the glass substrate 1 is rinsed with deionized water and blown dry with compressed air;
[0048] Then the glass substrate 1 is placed in a plasma cleaner for plasma cleaning for more than 2 minutes, and then cleaned with an Electronic Diener cleaner for more than 2 minutes; the Electronic Diener cleaner is a device that can be used to clean and disinfect medical equipment, laboratory equipment and other precision electronic equipment. This cleaner usually uses high-frequency sound wave technology and can effectively remove dirt on the surface of the equipment.
[0049] The deposition method of Ag-Cu alloy film includes:
[0050] Using electron beam evaporation technology, Ag, Cu and Ag-Cu alloy thin films are deposited on the glass substrate 1, with the purity of Ag being 99.99% and the purity of Cu being 99.999%;
[0051] The deposition of Ag and Cu was carried out on a Satis Vacuum model 725 equipment equipped with an ion gun and two electron beams;
[0052] Ag and Cu pellets were placed in two tungsten crucibles, and the substrate was fixed on a rotating bracket 530 mm away from the evaporation source;
[0053] During deposition, the pressure was 9.5×10 -6 mbar. During the evaporation process, an ion gun was used with an Ar flow rate of 13 sccm, and the pressure rose to 1.0×10 -4 mbar;
[0054] The glass substrate 1 is rotated at a speed of 9 rev / min and maintained at a temperature of 100° C.;
[0055] Film thickness was monitored using two independent quartz crystal monitors and later confirmed with a Bruker Dektak XT stylus profilometer;
[0056] The deposition rates of Ag and Cu were controlled by adjusting the deposition rate, and the chemical composition was finally confirmed by X-ray photoelectron spectroscopy.
[0057] The deposition parameters of TiO2 layer 5 by magnetron sputtering were as follows: power 4000 W, Ar flow rate 400 sccm, O2 flow rate 35 sccm, working pressure 5.0×10 -4 mbar, thickness is 39.7nm;
[0058] When the Ti layer 4 was deposited by magnetron sputtering, the deposition parameters were as follows: power 1200 W, Ar flow rate 400 sccm, working pressure 5.0×10 -4 mbar, thickness is 6.3nm;
[0059] When the SiO2 layer 6 was deposited by magnetron sputtering, the deposition parameters were as follows: power 2000 W, Ar flow rate 230 sccm, O2 flow rate 45 sccm, working pressure 3.3×10 -3 mbar, thickness is 10nm.
[0060] The spectral selectivity of the coating on LOW-E coated glass means that the coating can effectively block infrared and ultraviolet rays while maximally transmitting visible light. This feature requires precise control of the material and thickness of each layer when designing the coating to ensure that the coating has the ability to selectively transmit or reflect light of different wavelengths. Spectral selectivity is the core performance of LOW-E coating, which directly affects its energy-saving effect and visual comfort.
[0061] The treatment method of HC2 layer 7 includes:
[0062] A glass substrate 1 provided with a Ag-Cu alloy thin film layer 2, a PC / HC / TiO2 composite layer 3, a Ti layer 4, a TiO2 layer 5, and a SiO2 layer 6 was dip-coated using a dip coater, and then a transparent hard coating resin (HC2) was coated, which was a polysiloxane matrix embedded with silica nanoparticles. The dip-coated sample was vertically dried in a fume hood for 20 minutes and then baked at 130°C for more than 1 hour for curing.
[0063] Compared with the prior art, the LOW-E coated glass of this application has the following advantages:
[0064] Optical performance:
[0065] The 10nm thick Ag70Cu30 film has a solar-weighted transmittance in the visible range (TVIS) of 76% and a solar-weighted blocked light in the infrared range (BLIR) of 39%; it has high transmittance in the visible region and high reflectivity in the infrared region;
[0066] Good scratch and abrasion resistance:
[0067] The alloyed Ag70Cu30 film exhibits higher scratch and wear resistance than pure silver film; in the nano scratch test, the Ag70Cu30 film is superior to the pure silver film in adhesion to TiO2 and hardness;
[0068] Corrosion resistance:
[0069] The Ag70Cu30-based low-emissivity coating showed high corrosion resistance in the salt spray corrosion test, with little change in optical performance after 250 hours (TVIS decreased by 1%, RIR decreased by 11%), and no pitting corrosion. The pure silver-based coating began to corrode after 48 hours, and the optical performance decreased significantly after 250 hours (TVIS decreased by 15%, RIR decreased by 24%).
[0070] Environmental resistance:
[0071] The coated glass exhibits good weather resistance in acid rain and high-salt and high-humidity environments, and is suitable for low-emissivity coatings on the surfaces of automobiles and building windows.
[0072] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.
Claims
1. A high-efficiency heat-insulating LOW-E coated glass for building, characterized in that: The invention comprises a glass substrate, on which an Ag-Cu alloy thin film layer, a PC / HC / TiO2 composite layer, a Ti layer, a TiO2 layer, a SiO2 layer and an HC2 layer are sequentially arranged, the TiO2 layer, the Ti layer and the SiO2 layer are all deposited by a magnetron sputtering system, the Ag-Cu alloy thin film layer is deposited on the glass substrate by electron beam evaporation technology, the Ag-Cu alloy thin film layer is an Ag70Cu30 alloy thin film, and the thickness of the Ag-Cu alloy thin film layer is 10 nm.
2. The high-efficiency heat-insulating LOW-E coated glass for construction according to claim 1, characterized in that: The glass substrate processing method comprises: The glass substrate is placed in an ultrasonic cleaning machine and cleaned for more than 6 minutes using a solution prepared by Deconex and deionized water in a ratio of 3:97 to remove any impurities on the glass substrate; After cleaning, the glass substrate is rinsed with deionized water and blown dry with compressed air; Then, the glass substrate was placed in a plasma cleaner for plasma cleaning for more than 2 minutes, and then cleaned using an Electronic Diener cleaner.
3. The high-efficiency heat-insulating LOW-E coated glass for construction according to claim 1, characterized in that: The Ag-Cu alloy film deposition method comprises: Depositing Ag, Cu and Ag-Cu alloy thin films on the glass substrate using electron beam evaporation technology; The deposition of Ag and Cu was carried out on a Satis Vacuum model 725 equipment equipped with an ion gun and two electron beams; Ag and Cu pellets were placed in two tungsten crucibles, and the substrate was fixed on a rotating bracket 530 mm away from the evaporation source; During deposition, the pressure was 9.5×10 -6 mbar. During the evaporation process, an ion gun was used with an Ar flow rate of 13 sccm, and the pressure rose to 1.0×10 -4 mbar; The glass substrate is rotated at a speed of 9 rev / min and maintained at a temperature of 100° C.; Film thickness was monitored using two independent quartz crystal monitors and later confirmed with a Bruker Dektak XT stylus profilometer; The deposition rates of Ag and Cu were controlled by adjusting the deposition rate, and the chemical composition was finally confirmed by X-ray photoelectron spectroscopy.
4. The high-efficiency heat-insulating LOW-E coated glass for construction according to claim 1, characterized in that: When the TiO2 layer is deposited by magnetron sputtering, the deposition parameters are as follows: power 4000 W, Ar flow rate 400 sccm, O2 flow rate 35 sccm, working pressure 5.0×10 -4 mbar, and the thickness is 39.7nm.
5. The high-efficiency heat-insulating LOW-E coated glass for construction according to claim 1, characterized in that: When the Ti layer is deposited by magnetron sputtering, the deposition parameters are as follows: power is 1200 W, Ar flow rate is 400 sccm, working pressure is 5.0×10 -4 mbar, and the thickness is 6.3nm.
6. The high-efficiency heat-insulating LOW-E coated glass for buildings according to claim 1, characterized in that: When the SiO2 layer is deposited by magnetron sputtering, the deposition parameters are as follows: power is 2000 W, Ar flow rate is 230 sccm, O2 flow rate is 45 sccm, working pressure is 3.3×10-3 mbar, and thickness is 10 nm.
7. The high-efficiency heat-insulating LOW-E coated glass for buildings according to claim 1, characterized in that: The method for treating the HC2 layer comprises: The glass substrate provided with the Ag-Cu alloy thin film layer, the PC / HC / TiO2 composite layer, the Ti layer, the TiO2 layer, and the SiO2 layer was dip-coated using a dip coater, and transparent HC2 was coated. The dip-coated sample was vertically dried in a fume hood for 20 minutes and then baked at 130° C. for more than 1 hour to solidify.